CONTEXTUAL, CONCEPTUAL, AND PROCEDURAL KNOWLEDGE OF VOCATIONAL HIGH SCHOOL STUDENTS IN SOLVING DISTANCE CONTEXTS - Ai Tusi Fatimah; Nur Eva Zakiah; Yoni Sunaryo; Irfan Gumilar; Iyus Rusmana (Universitas Majalengka, 2020)
This study aims to describe the contextual, conceptual, and procedural mathematical knowledge of vocational students in solving mathematical tasks presented in the context of distance. This study used a qualitative approach by focusing on data collection techniques through interviews and observations. Participants involved in this study were 20 students of Vocational High School, Motorcycle engineering and business expertise, in Ciamis, Indonesia. Students solve the mathematical tasks on topics of equality and inequality of absolute values in the context of distance. The analysis is carried out on contextual, conceptual, and procedural knowledge by students. The results show that students who can connect contextual knowledge to their conceptual knowledge successfully solve mathematical tasks. This shows that contextual knowledge has the first role in determining the mathematical concepts needed in solving tasks, which are supported by procedural knowledge that will lead students to get the right solution.